Studi Evaluasi Manajemen Kebutuhan Area Parkir Kendaraan di Blang Padang, Kota Banda Aceh - Firman Maulana (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
The transportation problem that is often encountered in Indonesia is the limited road space needed to regulate traffic flow. In addition, there are also roads that operate at a much lower capacity than they should. One of the causes is on-street parking activities such as the Blang Padang area in the center of Banda Aceh City, Aceh Province. The purpose of this study is to evaluate the characteristics and management of parking areas in the Blang Padang area and to plan parking locations so that they can accommodate vehicles according to the required Parking Space Unit (SRP). This study uses a direct survey method to the field, namely collecting and compiling initial data, then explaining and analyzing the data so that conclusions can be drawn on the existing problems. The results showed that the design of vehicle parking in Blang Padang Jl. Prof. A. Majid Ibrahim II Banda Aceh City, namely for 2-wheeled there are 96 parking lots with a parking capacity of 72.00 m2 and for 4-wheeled vehicles there are 170 parking lots with a parking capacity of 425.00 m2.